Multiple and Persistent Inequalities in the Field of Assisted Reproduction - Viera Cherro, Mariana (Revista de Antropología Social, 2012)
This paper represents a first reflection on some of the changes taking place in the senses given to reproduction, sexuality and relationship from the existence and application of assisted reproductive technologies in the current Uruguay. We want to think about how these changes involve structural changes or changes of surface enable new inequalities on the geography of the old (Reygadas, 2008)